Interprofessional Communities of Practice in Continuing Medical Education for Promoting and Sustaining Practice Change: A Prospective Cohort Study. Issue 2 (2018) - Barker, Megan; Lecce, Julia; Ivanova, Anna; Zawertailo, Laurie; Dragonetti, Rosa; Selby, Peter
Abstract : Introduction: Standard knowledge delivery formats for CME may have limited impact on long-term practice change. A community of practice (CoP) is one tool that may enhance competencies and support practice change. This study explores the utility of an interprofessional CoP as an adjunct to a CME program in tobacco addiction treatment (Training Enhancement in Applied Counselling and Health [TEACH] Project) to promote and sustain practice change. Methods: A prospective cohort design was utilized to examine the long-term impact of the TEACH CoP on practice change. An online survey was administered to TEACH-trained practitioners to assess perceived feasibility, importance, and confidence related to course competencies, involvement in TEACH CoP activities, engagement in knowledge transfer (KT), and implementation of new programming. Chi-square tests were used to detect differences in KT and program development associated with CoP participation. Course competency scores from immediate postcourse surveys and long-term follow-up surveys were compared. Results: No significant differences in participant characteristics were found between those who did ( n = 300) and did not ( n = 122) participate in the TEACH CoP. Mean self-perceived competency scores were greater immediately after course than at long-term follow-up; however, self-ratings of competency in pharmacological interventions and motivational interviewing were higher at follow-up. TEACH CoP participation was associated with significantly greater engagement in KT and implementation of new programming after training. Discussion: The findings from this evaluation suggest the value of interprofessional CoPs offered posttraining as a mechanism to enhance practice. CME providers should consider offering CoPs as a component of training programs to promote and sustain practice change.